Richard Yates correspondence - Yates, Richard, 1815-1873.
Correspondence of Yates relating to Abraham Lincoln, the 1860 Republican National Convention and presidential election, the Emancipation Proclamation, and other political affairs. Correspondents include Schuyler Colfax, William Henry Herndon, and Nathaniel McLean. Includes typewritten transcripts of the correspondence.
Illinois governor and U.S. representative and senator from Illinois.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Colfax, Schuyler, -- 1823-1885 -- Correspondence; Herndon, William Henry, -- 1818-1891 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; McLean, Nathaniel, -- 1815-1905 -- Correspondence; Emancipation Proclamation; Elections -- United States -- 1860.; Slavery -- United States; Slaves -- Emancipation -- United States; United States -- History -- Civil War, 1861-1865 -- African Americans; United States -- Politics and government -- 1857-1861.; United States -- Politics and government -- 1861-1865.; Governors -- Illinois; Representatives, U.S. Congress -- Illinois; Senators, U.S. Congress -- Illinois